AN EVALUATION OF LANGUAGE LEARNING STRATEGIES USED BY ENGLISH STUDENTS - Bunga Ayu Wulandari (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
This research investigates the language learning strategies used by English students of Faculty of Teacher Training and Education (FKIP, hereafter) of Universitas Jambi. This research employed the Strategy Inventory for Language Learning (SILL) questionaires designed by Oxford (1990) to obtain data from 85 students of the fifth semester class 2015 studying at the English Department. The statistical analysis of the data revealed that students opted for metacognitive (Part D), social (Part F), cognitive (Part B), compensation (Part C), memory (Part A), and affective (Part E) strategies respectively as the most strategies they have used most in their language learning process. This finding shows that teachers can actually assess their students’ view about their learning strategies. This finding implies that teachers should be aware that students have different preferences to learn so that teachers need to be prepared to conduct variety of teaching strategies in their classrooms as well as emphasing the importance of learners’ metacognitive strategies without leaving out the other learning strategies. ABSTRAKRiset ini menginvestigasi strategi pembelajaran Bahasa Inggris yang digunakan oleh mahasiswa-mahasiswa Prodi Bahasa Inggris pada Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas jambi. Riset sekarang ini menggunakan kuestioner the Strategy Inventory for Language Learning (SILL) yang didesain oleh Oxford (1990) untuk memperoleh data dari 85 mahasiswa-mahasiswa semester 5 kelas 2015 yang belajar pada Prodi Bahasa Inggris. Data statitis menunjukkan mahasiswa-mahasiwa memilih strategi metacognitive (Part D), social (Part F), cognitive (Part B), compensation (Part C), memory (Part A), dan affective (Part E) berturut-turut sebagai strategi yang paling sering digunakan dalam proses pembelajaran Bahasa Inggris mereka. Temuan ini menunjukkan bahwa guru dapat menilai pandangan siswa-siswa tentang strategi pembelajaran bahasa. Temuan ini juga mengimplikasikan bahwa guru semestinya menyadari bahwa siswa memiliki pilihan-pilihan yang berbeda dalam belajar sehingga guru perlu mempersiapkan berbagai macam variasi strategi mengajar dalam kelas sekaligus menekankan pentingnya strategi metacognitive pada siswa tanpa mengabaikan strategi pembelajaran bahasa lainnya. How to Cite: Wulandari, B. A. (2018). An Evaluation of Language Learning Strategies Used by English Students. IJEE (Indonesian Journal of English Education), 5(1), 16-25. doi:10.15408/ijee.v5i1.8460